وہاب اشرفی کی تاریخ اور ادب پر تنقید ؛ ایک متنازعہ نقطہ نظر: WAHAB ASHRAFI'S CRITICISM OF HISTORY AND LITERATURE; A CONTROVERSIAL PERSPECTIVE (Al-Aasar, 2025)
Literary historiography is not merely a chronological record of the past but a dynamic intellectual dialogue between history and criticism. This research article explores the multifaceted scholarly persona of Professor Wahab Ashrafi, specifically focusing on his role as a critic within the realm of history writing. Centered on his magnum opus, Tarikh-e-Adab-e-Urdu (History of Urdu Literature), the study analyzes how Ashrafi deviated from traditional descriptive methods to establish a "Critical History" that evaluates literary works within their socio-political and psychological contexts. The article highlights his courageous and controversial decision to include living contemporary writers, his defense of the neglected Dabistan-e-Azimabad against regional biases, and his intellectual confrontations with established critics like Kalimuddin Ahmad regarding the stature of humorists like Patras Bukhari. Furthermore, the research objectively examines the scholarly debates surrounding his work, including technical discrepancies in dates, the authenticity of early Sufi attributions, and the initial structural omissions of pivotal figures such as Allama Iqbal and Shibli Nomani. The study concludes that while Wahab Ashrafi’s work is an invaluable, up-to-date encyclopedic resource characterized by critical boldness and stylistic simplicity, it requires careful verification by researchers concerning factual precision and chronological consistency.